The impact of digital inclusion on metamemory, quality of life and mood in healthy elderly people - Alvim, Kelly Cristina Barbosa Levi (2021)
The objective of this quantitative and cross-sectional study was to verify the effects of digital inclusion in elderly people. Twenty-five elderly people (M=64.92 years; SD= ±3.74) were evaluated in sociodemographic, psychological and cognitive measures. Analyzes indicated statistically significant changes in anxiety (p=0.53) and depression (p=0.36). There was a trend in the psychological domain (p=0.07) in the relationship between quality of life and mood. In this context, the technology had a negative impact on metamemory, positively on some quality of life variables and without statistically significant changes in mood states.